2017
DOI: 10.1093/mnras/stx1990
|View full text |Cite
|
Sign up to set email alerts
|

Tails and bridges in the parabolic restricted three-body problem

Abstract: After a close encounter of two galaxies, bridges and tails can be seen between or around them. A bridge would be a spiral arm between a galaxy and its companion, whereas a tail would correspond to a long and curving set of debris escaping from the galaxy. The goal of this paper is to present a mechanism, applying techniques of dynamical systems theory, that explains the formation of tails and bridges between galaxies in a simple model, the so-called parabolic restricted three-body problem, i.e. we study the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As collisions are taken into consideration in this paper, in a majority of prograde cases the boundaries are always collision regions. In References [48,49], without considering collisions, the authors numerically demonstrated that the boundaries between different regions should be the invariant manifolds related to + , which trend to as → +∞. This point can provide further insights into the ICMs.…”
Section: Regions Of Capturementioning
confidence: 86%
See 2 more Smart Citations
“…As collisions are taken into consideration in this paper, in a majority of prograde cases the boundaries are always collision regions. In References [48,49], without considering collisions, the authors numerically demonstrated that the boundaries between different regions should be the invariant manifolds related to + , which trend to as → +∞. This point can provide further insights into the ICMs.…”
Section: Regions Of Capturementioning
confidence: 86%
“…The third body 3 , a massless particle, moves under the gravitational field generated by the primaries and orbits in the same plane as the primaries, without perturbing them. The problem described above is the planar parabolic restricted three-body problem (PPRTBP) [46][47][48][49]52]. Considering a binary asteroid pair approaching a central body, we can approximate the dynamics of the problem through PPRTBP, denoting the central body as 1 , the main asteroid as 2 and the minor asteroid as 3 , as shown in Fig.…”
Section: Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first simulations of galaxy gravitational interaction by Toomre and Toomre [17] demonstrated a rich collection of tails and bridges formed even without gas participation in the interactions. Later, a significant amount of other simulations were made, both pure N-body ones (e.g., [18,19]) and those taking into account gas dynamical effects in gas-rich galactic disks (e.g., [20][21][22]), and outer tails and bridges were obtained in these simulations providing gas exchange between interacting galaxies. The observations of some spectacular interacting galaxy systems also demonstrated extended outer gaseous structures, connecting the interacting galaxies-sometimes those formed from cold neutral hydrogen and seen only in the 21 cm line without optical counterparts [23][24][25], and sometimes star formation was detected in these structures beyond the galactic disks, and they were excited by young stars and seen both in UV [26] and in the ionized-gas optical emission lines (e.g., [27][28][29][30]).…”
Section: Introductionmentioning
confidence: 99%